Quitters would not prosper: Examining the relationship between online assessment performance and assessment attrition behavior. (14th October 2020) - Hardy, Jay H.; Gibson, Carter; Carr, Alison; Dudley, Nikki
Abstract: Hiring managers are often hesitant to implement online assessments over concerns that higher‐quality candidates are more likely to quit lengthy assessment batteries than lower‐quality candidates. In this paper, we present the results of two studies that collectively challenge this assumption. In Study 1, data from 327, 517 job‐seekers spanning eight hiring contexts showed that assessment performance was negatively associated with subsequent assessment attrition behavior. In Study 2, we replicated this pattern of effects in two additional samples comprising 1, 844, 604 applicants for hourly associate positions, and 18, 937 applicants for nursing positions. Collectively, these findings suggest that some degree of attrition may ultimately benefit, rather than harm, organizations using prehire assessments.